Community Engagement: A Critical Guide for Practitioners: Chapter 6: Defining the Problem - Framing the Solution (Concept: The Journal of Contemporary Community Education Practice Theory, 2018)
Cristina Asenjo introduces Chapter 6 of Community Engagement: A Critical Guide for Practitioners byJim Crowther and Mae Shaw